Exploring the Nexus of Electricity Supply and Economic Growth in South Africa - Khobai, Hlalefang; Mugano, Gift; Le Roux, Pierre (International Journal of Energy Economics and Policy, 2017)
This paper investigates the causal relationship between electricity supply and economic growth in South Africa using annual data covering the period between 1985 and 2014. This paper used a multivariate framework which included trade openness, electricity price, capital and employment as intermittent variables. The ARDL bound testing was employed to establish the long run relationship between these variables. The Vector Error Correction Model (VECM) was estimated to carry out the test of causality. The results support the existence of co-integration among the variables. The VECM established a bidirectional causality flowing between electricity supply and economic growth. This shows that the policy makers should prioritise building capacity additions and infrastructure development of the South African electricity supply industry, as this will stimulate economic growth and increase electricity in the country. The findings further show that electricity prices, trade openness, employment and capital Granger-cause economic growth and electricity supply. This result means that increased economic growth and electricity supply is dependent on the degree of trade openness, employment levels in the country and the amount of investment. Keywords: Electricity supply; Economic growth; South Africa; Causality JEL Classifications: Q32, Q43